PERBANDINGAN LATAR, IDEOLOGI, DAN COVER DALAM NOVEL JONI GARANG PERANG DINGIN DAN SI ALUI - Sukarjo Waluyo; Redyanto Noor; Ary Setyadi (Endogami: Jurnal Ilmiah Kajian Antropologi, 2022)
The research titled “The Comparison of Setting, Ideology, and cover in the novel of Joni Garang Perang Dingin and Si Alui” intends to tell a different setting role from the two novels that caused the two of different ideology to occur. As well as the different of the books cover as a representative of a book content. From the structural between aspects involvement of the two novels, we can see there is cohesiveness between aspects in totality purpose building. However, the focus of structural analysis is the story setting study. Sociologically, both of the novels are very interesting because they are able to give different ideology. This is because the writer takes sides in choosing different points of view which often appears nowdays, for instance a modern ideology versus traditional ideology